Dividend payment policy across food industry companies – the case of European economies - Mądra-Sawicka, Magdalena (Polityka wypłaty dywidendy w przedsiębiorstwach przemysłu spożywczego na przykładzie gospodarek europejskich, 2020)
The purpose of the paper is to examine the factors influencing the dividend payout policy. Our analysis is based on unbalanced panel data with 4 582 observations of companies from 35 countries over 20 years, 1999-2018. The study covers the companies that are listed on European stock exchange and also includes countries that are not in the EU. The factors that influence the dividend payment decision were identified. The advantage of a positive relationship between dividend payout is based mostly on the previous dividend payout decision. This shows the need to continue the undertaken dividend policy which reflects investors’ expectations in this sector. Overall, the evidence supports that the productivity of a food sector companies’ impact on the decision of dividend payment is even stronger that the level of profitability and size of a company. The debt level has a negative relationship with the dividend payout ratio. However, its impact was weak, mostly because of the low debt level in the case of food sector companies. Our evidence supports the agency and information asymmetry theory and contributes to international business research across intra-industry dividend policy characteristics
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2020; vol. 64, nr 4, s. 146-159
Keywords: dividend policy; emerging economies; developed economies; panel tobit model; food sector; polityka dywidendowa; gospodarki rozwijające się; gospodarki rozwinięte; model panelowy; sektor spożywczy